2021
DOI: 10.1021/acs.est.1c02095
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Atmospheric Oxygenated Organic Compounds to Particle Growth in an Urban Environment

Abstract: Gas-phase oxygenated organic molecules (OOMs) can contribute substantially to the growth of newly formed particles. However, the characteristics of OOMs and their contributions to particle growth rate are not well understood in urban area, which has complex anthropogenic emissions and atmospheric conditions. We performed long-term measurement of gas-phase OOMs in urban Beijing during 2018-2019 using nitrate-based chemical ionization mass spectrometry. OOM concentrations showed clear seasonal variations, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
109
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(123 citation statements)
references
References 73 publications
14
109
0
Order By: Relevance
“…However, the reduction of PM2.5 was considerably weaker than those of the primary pollutants, and in some cities such as Beijing, the PM2.5 concentrations even increased after the lockdown policy was imposed (Huang et al, 2021). This persistent particulate pollution has been attributed to both unfavorable meteorology, such as stagnant meteorological conditions and high relative humidity (RH) (Le et al, 2020;Wang et al, 2020b) and to enhanced atmospheric oxidative capacity caused by increased O3 and NO3 radical formation (Huang et al, 2021;Le et al, 2020). To date, few studies have focused on either atmospheric new particle formation or the overall particle number size distribution (Shen et al, 2021a;Shen et al, 2021b) during the lockdown period, although NPF has been shown to enhance haze formation (Guo et al, 2014;, and the particle number size distribution is known to influence the health effect of particles (Harrison et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the reduction of PM2.5 was considerably weaker than those of the primary pollutants, and in some cities such as Beijing, the PM2.5 concentrations even increased after the lockdown policy was imposed (Huang et al, 2021). This persistent particulate pollution has been attributed to both unfavorable meteorology, such as stagnant meteorological conditions and high relative humidity (RH) (Le et al, 2020;Wang et al, 2020b) and to enhanced atmospheric oxidative capacity caused by increased O3 and NO3 radical formation (Huang et al, 2021;Le et al, 2020). To date, few studies have focused on either atmospheric new particle formation or the overall particle number size distribution (Shen et al, 2021a;Shen et al, 2021b) during the lockdown period, although NPF has been shown to enhance haze formation (Guo et al, 2014;, and the particle number size distribution is known to influence the health effect of particles (Harrison et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The reductions of primary emissions mitigated particulate pollution and improved air quality in many countries around the globe (Sicard et al, 2020;Krecl et al, 2020;Agarwal et al, 2020;Ciarelli et al, 2021), including many Chinese cities (Wang et al, 2020b;Huang et al, 2021;Le et al, 2020). However, the reduction of PM2.5 was considerably weaker than those of the primary pollutants, and in some cities such as Beijing, the PM2.5 concentrations even increased after the lockdown policy was imposed (Huang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations